Classroom politics - Želježič, Mirjana (ELOPE (Ljubljana), 2013)
What we are faced with at present is a blatant neoliberal transformation of universities, whose social relevance depends increasingly on the ability to serve the needs of neoliberal capitalism. If we see this as a problem - as many of us do - then we also feel the need to defend (and develop) the traditional practices of universities, such as "pure" research and critical reflection on society. Yet such a response, inevitably, goes hand in hand with critique of and struggle against ideology behind capitalism itself, against the logic of competition and prot. Drawing on the legacy of Freire and Althusser, the article highlights some of the links between the English language teaching and the neoliberal politics, and gives suggestions about ways in which departments of English in general, and language classes in particular, can be a part of the socially critical forces rather than a part of the so-called liberal-progressive camp.
Keywords: Freire, Paulo; ideologija; jezik; kritična pedagogika; Language; neoliberalizem